Modeling the Impacts of Corporate Environmental Responsibility on Information and Communication Technology -waste Management - Tan, Mei-Chee; Ng, Tuan-Hock; Lim, Ying-San; Lye, Chun-Teck; Ismail, Hishamuddin (International Journal of Energy Economics and Policy, 2018)
The global growth of consumption and disposal of information and communication technology (ICT) appears to be one of the main factors that fuels the increased level of ICT-waste. With ICT-waste causing environmental degradation, there is urgency in the public interest to achieve more sustainable development. This study develops a conceptual framework for reduce behavior at workplace premised on the classic theory of planned behavior (TPB). The theoretical contribution of this study is primarily upon expanding existing knowledge on factors influencing pro-environmental behaviors, by firstly conceptualizing reduce behavior and secondly emphasizing the mediating effect of corporate environmental responsibility (CER) on the relationships between attitude, subjective norms and perceived benefits, and reduce behavior. In short, a well-communicated environmental policy within organizations is urgently required, being a strong signal that encourages employees to engage in pro-environmental actions. Keywords: reduce, corporate environmental responsibility, ICT-waste, theory of planned behavior JEL Classification: P28